Comparison of technical and commercial aspects regarding cold forming, superplastic forming and hot deep drawing: Vergleich technischer und wirtschaftlicher Aspekte beim Kaltformen, superplastischem Umformen und Warmtiefziehen. Issue 10 (19th October 2017) - Beck, W.; Wagner, S.; Schauer, K.
Abstract: Titanium parts can be very expensive or can be a good compromise between cost and efficiency especially when expected cost and weight reduction is reached or exceeded. Titanium properties are always well desired but the high level of material cost and the cost of manufacturing are not appreciated. Applicable forming processes for sheet metal parts range from conventional cold forming of commercially pure titanium with subsequent separate annealing up to hot forming processes like hot bending, hot calibration, hot deep drawing and superplastic forming with in‐process annealing. Each process has limitations and/or special advantages. There are big differences in material waste, cycle time, process cost, overweight from minimum wall thickness requirements and tool design. Suitable choice of process and the technical feasibility is mostly depending on part geometry also in respect of constant wall thickness and type of alloy. The paper describes decision guidelines to find the right process for a given inquiry concerning alloy, service loads, number of load cycles, temperature, quantity, optical appearance, etc. The total picture has to include the following assembly processes. Some representative solutions are described.